2017
DOI: 10.1021/acs.jmedchem.7b00291
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of N6-Substituents in Potent Dual Acting 5′-C-Ethyltetrazolyladenosine Derivatives: Synthesis, Binding, Functional Assays, and Antinociceptive Effects in Mice

Abstract: Structural determinants of affinity of N6-substituted-5′-C-(ethyltetrazol-2-yl)adenosine and 2-chloroadenosine derivatives at adenosine receptor (AR) subtypes were studied with binding and molecular modeling. Small N6-cycloalkyl and 3-halobenzyl groups furnished potent dual acting A1AR agonists and A3AR antagonists. 4 was the most potent dual acting human (h) A1AR agonist (Ki = 0.45 nM) and A3AR antagonist (Ki = 0.31 nM) and highly selective versus A2A; 11 and 26 were most potent at both h and rat (r) A3AR. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Nucleotide and nucleoside analogues synthesized from the α-D-ribofuranose sugar moiety have previously shown anti-nociceptive activity to some extent ( 10 ). Several nucleoside analogues had also demonstrated analgesic activity in a number of antinociceptive assays such as thermal nociception test ( 25 ), formalin induced paw screening assay ( 26 ) and the hot plate test ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide and nucleoside analogues synthesized from the α-D-ribofuranose sugar moiety have previously shown anti-nociceptive activity to some extent ( 10 ). Several nucleoside analogues had also demonstrated analgesic activity in a number of antinociceptive assays such as thermal nociception test ( 25 ), formalin induced paw screening assay ( 26 ) and the hot plate test ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide and nucleoside analogues synthesized from the α-D-ribofuranose sugar moiety have previously shown potent antinociceptive activity without any side effects ( 10 ). Chemically modified small interfering RNAs (siRNAs) containing ribofuranose sugar moiety in the 3’-overhang region seemed to have increased nuclease resistance and knockdown effect generating great interest in the field of RNA interference-based therapeutics ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the selective pharmacological stimulation of the A 3 AR induced pronounced and prolonged antiallodynic effects in traumatic nerve-injury, chemotherapyinduced and other models of neuropathic pain (Bar-Yehuda et al, 2011;Chen et al, 2012;Fishman et al, 2012;Janes et al, 2015;Little et al, 2015;Tosh et al, 2015;Terayama et al, 2018;Wahlman et al, 2018;Stockstill et al, 2020). Moreover, A 3 ARselective agonists reduced the formalin-induced nocifensive behaviour and diabetic neuropathy (Yan et al, 2016;Petrelli et al, 2017). The A 3 AR seems to exert its beneficial effect at different levels of the pain axis.…”
Section: A 3 Adenosine Receptor In Chronic Painmentioning
confidence: 99%
“…Combining a 5′-C-ethyltetrazol-2-yl moiety with the appropriate N 6 -substitution in adenosine derivatives, an increased affinity versus both h A 1 AR and h A 3 AR (at the subnanomolar range) was achieved while remaining agonists at h A 1 AR and antagonists at h A 3 AR. The follow-up paper aimed to extend the series of 5′-C-(ethyltetrazol-2-yl)adenosine and 2-chloroadenosine derivatives, modifying the substituent in the N 6 -position of the adenine ring [ 137 ]. This study demonstrated for the first time that all dual-acting N 6 -substituted 5′‑C‑ethyl-tetrazolyl adenosine derivatives act as antagonists at human A 3 AR but as agonists at the rat A 3 AR, highlighting the importance of species differences for both affinity and efficacy at A 3 AR.…”
Section: Rationale For Treating Ocular Diseases Via Adenosine Receptomentioning
confidence: 99%